2016
DOI: 10.15282/jmes.10.3.2016.6.0212
|View full text |Cite
|
Sign up to set email alerts
|

Numerical investigation of soot mass concentration in compression ignition diesel engine

Abstract: Soot particles, carbon monoxide, oxides of nitrogen, oxides of sulphur, and hydrocarbon are the emissions produced from diesel engine combustion. Those emissions species are undesirable since they give detrimental impacts to the atmosphere and human well-being. Several numerical investigations conducted by various researchers provide different soot mass concentration values. As an alternative, this study was carried out to investigate the soot mass level produced by a single cylinder diesel engine, using a com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 50 publications
(46 reference statements)
0
13
0
Order By: Relevance
“…Both shorter ignition delay and better atomization were responsible for complete combustion and reduced HC emissions. It was also observed that at oxygen percentages higher than 2.37% (blend number [13][14][15][16][17][18], HC emissions were better than those of other fuel blends, with fuel blend number 18 showing the lowest HC emission.…”
Section: Hc Emissionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both shorter ignition delay and better atomization were responsible for complete combustion and reduced HC emissions. It was also observed that at oxygen percentages higher than 2.37% (blend number [13][14][15][16][17][18], HC emissions were better than those of other fuel blends, with fuel blend number 18 showing the lowest HC emission.…”
Section: Hc Emissionsmentioning
confidence: 99%
“…Moreover, biodiesel is more advantageous in comparison to diesel fuel due to its higher flash point, lower volatility, and greater lubricity [2,[12][13][14][15]. Besides that, biodiesel has a lower aromatic compound content, contains 10%-12% oxygen by weight, and is free of sulphur content.…”
Section: Introductionmentioning
confidence: 99%
“…Subscripts sf and sc, in the above equations, represent soot formed and consumed, respectively. The values of activation energies (represented by Esf and Esc) were taken as 82 X 10 6 and 120 X 10 6 respectively. mfb represents the mass of fuel burnt at every crank angle step and was determined by using the following expression.…”
Section: Sub-model For Soot Formationmentioning
confidence: 99%
“…A higher expansion ratio due to high compression ratios in diesel engines leaves low thermal energy to the exhaust, resulting in low fuel consumption and high power output [1,2]. However, diesel engines produce higher levels of nitrogen (NOx) oxides and particulate matter (PM) or soot as compared to their counterpart spark ignition (SI) engines [3][4][5][6]. This is due to diesel engines heterogeneous combustion and thus results in a complex unresolved trade-off between NOx and soot emissions [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation